Comparative Perspectives on the Role of National Pride, Identity and Belonging in the Curriculum - Camille Kandiko Howson; Marie Lall (MDPI AG, 2022)
In this Special Issue, Comparative Perspectives on the Role of National Pride, Identity and Belonging in the Curriculum, Pedagogy and Experience of Higher Education, papers explore how contemporary issues in democratic education play out in higher education curriculum policy, pedagogy, and the student experience within and across different national contexts [...]